Sustainable High Volume Road and Rail Transport in Low Income Countries - Burrow, Michael; Ghataora, Gurmel; Thompson, Bruce; Obika, Bernard (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents an in-depth analysis of transport research commissioned by the UK Department for International Development under the High Volume Transport Programme (2017-2023). The analysis done in the period 2018-2019 contributes to the UK response to improving transport in the low-income countries in Africa and South Asia. As a result, key priorities have been identified for applied research in 2020 to make road, rail and urban transport more efficient and affordable, and all transport greener, safer and more inclusive for all users. This applied research is a vital link in making transport a sustainable lifeline for people in low-income countries, because transport gives farmers and manufacturers access to domestic and international markets and people in rural and urban areas access to schools and health services.